Project management office: proposal for a company in the industrial branch of highways and ore extraction - Bonato, Samuel Vinicius; Gandin, Fernanda Fagundes; Ribeiro, Luciano Maciel; Pereira Junior, Errol Fernando Zepka (Brazilian Journal of Production Engineering, 2021)
The present research. aims to assess the current situation of the company studied with respect to project management and propose a model more suitable for its structure, since this organization uses a large part of its budget in various types of projects and does not have a defined process for managing them. This research was carried out at a company in the industrial sector, manufacturer, and dealer of machinery for paving roads and mining ore. Based on the research, it can be said that there is no single formula for implementation or even a single model of PE: each organization can develop a specific configuration, based on its characteristics, resources and knowledge. It is concluded that the implementation of a Project Management Office appropriate to the structure of the company, will bring concrete benefits for it, providing greater control over the investments employed in business projects and disseminating knowledge in project management across the company. In view of the comparison presented, it was possible to identify how much the company lost in the inadequate execution of the second project, where the cost exceeded 107% and the term in 48 working days of the planned. It is proposed that the company implements the Project Management Office according to the model elaborated in this research, whose characteristics were based on the MMGP methodology and, follow up the activities during the first year of operation.
Keywords: Projects; Project Management Office; Industry; highways; ore extraction.